Will systematic reviews facilitate translational behavioral ecology? With a few conditions: a comment on Berger-Tal et al. (14th November 2018) - Griffin, Andrea S; Hayward, Matt W
Abstract : With a few safeguards in place, systematic reviews offer exciting new prospects to behavioral ecology. We need to ensure that conservation interventions are evaluated and outcomes disseminated and that journal outlets willing to publish species-specific knowledge do not disappear as these will form repositories of information available to the review process. We also need to ensure that systematic reviews are protected against conflicts of interest and that methodologies are taught in undergraduate programs